Splenectomy Versus Sham Splenectomy in a Swine Model of Controlled Hemorrhagic Shock. Issue 4 (October 2016) - Boysen, Søren R.; Caulkett, Nigel A.; Brookfield, Caroline E.; Warren, Amy; Pang, Jessica M.
ABSTRACT: Introduction: Splenectomy is controversial in acute hemorrhagic shock models. Objective: To compare splenectomized (SP) versus sham-splenectomized (SSP) swine during acute controlled hemorrhage. Methods: Twenty-six male Landrace White swine (mean body weight ± standard deviation, 33.8 ± 2.9 kg) were used. Ethics approval was obtained. Landrace swine underwent splenectomy (n = 13) or sham-splenectomy (n = 13), were bled to mean arterial blood pressure (MAP) of 40 mm Hg, which was held for 60 min, given 125 mL IV RescueFlow, held for a further 60 min, given whole blood, and held for a final 60 min. Tissue oxygen saturation, thromboelastography, oncotic pressure, urine volume and specific gravity, complete blood count, serum chemistry, body temperature, hematocrit, total solids, arterial and mixed venous blood gas, bispectral index, SAP, MAP, DAP, cardiac index, total blood volume (TBV) removed and returned, rate of hemorrhage and transfusion, spleen weight, heart rate (HR), arterial pH, lactate, PaO2, PaCO2, respiratory rate, cranial mesenteric and renal artery blood flow were recorded. Groups were compared using two-way ANOVA with post hoc Bonferroni ( P  < 0.05) for repeated measures or t test for non-repeated measures. Results: Compared with the SSP swine, SP swine had higher HR post-splenectomy for the duration of the experiment ( P  < 0.03), and higher hematocrits at 15 and 60 min post splenectomy ( P  < 0.01, P  < 0.001, respectively). SSP swine had greater TBV removed during hemorrhage ( P  < 0.01); however, when blood loss based on splenic weight was considered, TBV removed was similar between groups. Conclusion: Splenectomy likely accounts for the transient increase in hematocrit and the higher HR in SP swine prior to hemorrhage, and the differences in TBV removed between the two groups during hemorrhage. With a fixed end point model using a moderate rate of acute hemorrhage and an MAP of 40 mm Hg, splenectomy is not necessary and may confound results.